The Effect of Increased Sight Word Knowledge on the Comprehension of Below Level Third Grade Readers - Serio, Nanette (My University, 2014)
The purpose of this study was to determine whether increasing sight word knowledge in below level third grade readers impacts their comprehension of a simple text. The intervention implemented was the repeated use of flash cards with the first through third grade Dolch words, 20 minutes of daily guided reading instruction, interactive games and websites students practiced with during independent time, and homework assignments focused on the sight word practice. The measurement tools used were the 128 Dolch words from first, second, and third grade lists and a passage containing all 220 common Dolch sight words for a pre- and post-test comprehension assessment. This study involved the use of a quasi-experimental, pretest/posttest repeated measures design to compare data from before the intervention was implemented in February 2014 to data from after the intervention was implemented in April 2014. Achievement gains in sight word knowledge were apparent for all students involved in the study. Findings of the study may have been influenced by intervening factors such as changes in classroom schedules, parent involvement at home or questions of validity with the assessment. Research in the area of sight word knowledge should continue given the relationship between the sight word recognition and increased reading comprehension.
Keywords: Education -- Research papers (Graduate); Reading (Elementary) -- Research; Reading comprehension -- Research; Word recognition -- Research